MAPPING DRYNESS TIME-SCALES IN THE CURVATURE CARPATHIANS AND SUBCARPATHIANS (ROMANIA) BY THE STANDARDIZED PRECIPITATION INDEX - ANDUŢA GROFU; CARMEN-SOFIA DRAGOTĂ; CĂTĂLINA MĂRCULEŢ; LOREDANA-ELENA MIC (Revue Roumaine de Géographie)
In order to identify and describe deficitary precipitationhazards in the Curvature Carpathians and Subcarpathians, as well as excess of precipitation anomalies versus mean values, Standardized Precipitation Index (SPI) values were analysed over a period of 12 consecutive months during the 1961 … 2000 interval. Homogeneous data were recorded at the Bisoca, Lăcăuţi, Întorsura Buzăului, Pătărlagele, Penteleu and Ploieşti stations. SPI values are agood indicator for determining and characterising deficitary precipitation. The results obtained were synthetised on maps of SPI territorial distribution values (%) of the extreme dry class, namely, the two sub-classes: moderately dry (-2 ... -2.5) and extremely dry (<-2.5). The share of each analysed SPI value set is illustrated on graphs